Ingen panik - Iran kan balanceres - Rahigh-Aghsan, Ali (Politik, 2010)
The majority view among Iran watchers and experts on the Middle East is that Iran is a rising power that poses an increasing threat to regional and even global security. This article takes issue with this view arguing that the rise of Iran and the threat it poses has been vastly exaggerated. There is no reason to panic - Iran will not be as dominant as some experts believe, and its ability to threaten the Persian Gulf let alone the Middle East is not as great as feared. Even an Iran armed with nuclear weapons can be contained and balanced. Bombing Iran would therefore be a major mistake.